Effectiveness of Methadone Maintenance Therapy (MMT) and life style improvement among opiate dependent patients registered - Christina Malini,; Noor Azizah Abdul Wahab,; Ahmad Fuad Shamsuddin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In Malaysia, drug addiction has been a big threat since 1983. As of by latest statistic by National Anti-Drug Agency in 2016, the number of drug abusers in Malaysia was 30846. Acknowledging the importance of drug abuse and relapse as a public health issue, Malaysian government had implemented Harm Reduction Programme .Under this programme, Methadone Maintenance Therapy (MMT) was launched in Oct 2005. This study was undertaken to evaluate the effectiveness of MMT programme among opiate dependent individuals in their daily life. In this study, 100 individuals from the Ministry of Health (MoH), Klinik Kesihatan Bayan Lepas (Bayan Lepas Health Clinic) and Agensi Anti-Dadah Kebangsaan (National Anti-Drug Agency) in Telok Bahang were involved. The subjects were interviewed with WHOQOL BREF questionnaires before joining the MMT programme and also after minimum 4 months of joining MMT. Results obtained were used for comparing life style implications among methadone patients before and after joining the MMT programme. Subjects were predominantly of Malay ethnicity (82%). Subjects were mostly aged between 51 to 60 years old (34%). Paired t-test was done on the WHOQOL scores at baseline (before MMT) and after minimum of 4 months enrolment for all four domains. Each domain showed significant improvement in QOL (P < 0.05).The highest improvement was shown in the psychology domain with the mean value increment of 15.13 ± 17.49. Physical domain showed the least improvement with the mean value of 9.39 ± 16.21.This study has proven that MMT have highly contributed to improvement of quality of life among MMT clients in Klinik Kesihatan Bayan Lepas and AADK Telok Bahang.